2022
DOI: 10.3389/fonc.2022.900671
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of DEAH-Box Helicases Relate to Poor Prognosis and Reduction of DHX9 Improves Radiosensitivity of Hepatocellular Carcinoma

Abstract: BackgroundLiver hepatocellular carcinoma (LIHC), one of the most common primary malignancies, exhibits high levels of molecular and clinical heterogeneity. Increasing evidence has confirmed the important roles of some RNA helicase families in tumor development, but the function of the DEAH-box RNA helicase family in LIHC therapeutic strategies has not yet been clarified.MethodsThe LIHC dataset was downloaded from The Cancer Genome Atlas (TCGA). Consensus clustering was applied to group the patients. Least abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The landscape of mutations indicated that DHX9, NLRP3, and NLRP7 showed the highest frequency of mutations. Interestingly, previous study also found that DHX9 had a high expression level and ampli cation mutation frequency in HCC and was effective on DNA damage repair (27).…”
Section: Discussionmentioning
confidence: 91%
“…The landscape of mutations indicated that DHX9, NLRP3, and NLRP7 showed the highest frequency of mutations. Interestingly, previous study also found that DHX9 had a high expression level and ampli cation mutation frequency in HCC and was effective on DNA damage repair (27).…”
Section: Discussionmentioning
confidence: 91%
“…DHX9, as an NTP-dependent helicase protein, plays a vital role in varieties of cellular processes, and aberrant DHX9 expression participates in multiple human diseases ( 14 , 15 ) including various cancers, e.g. colorectal cancer (CRC) ( 16 ), hepatocellular carcinoma ( 9 ), and prostate cancer ( 7 ). In a variety of clinical and translational studies, DHX9 was confirmed as a prognostic gene for cancers.…”
Section: Discussionmentioning
confidence: 99%
“…( 18 ) reported significant infiltrations of macrophages, dendritic cells, and neutrophils in gastric cancer patients with high DHX9 expression. In HCC, the six DEAH-box RNA helicases in the contrasted risk model were substantially associated with immune inhibitors and innate immune cell infiltrations ( 9 ). In addition, Jiao et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of DDX23 is enhanced in glioma tissues, and this is associated with poor survival of glioma patients ( 92 ). In computational analyses of 15 DEAH-box RNA helicases, elevated expression of 12 of them are associated with poor prognosis and worse clinical features in hepatocellular carcinoma ( 111 ). Because of their overarching role in RNA metabolism, DEAD/H-box helicases are likely to affect multiple aspects of cell behaviors, including cell proliferation, which may lead to cancer development.…”
Section: Abnormal Expression Of Dead/h-box Helicases In Cancermentioning
confidence: 99%